2020
DOI: 10.1038/s41372-020-00805-w
|View full text |Cite|
|
Sign up to set email alerts
|

Difference in levels of SARS-CoV-2 S1 and S2 subunits- and nucleocapsid protein-reactive SIgM/IgM, IgG and SIgA/IgA antibodies in human milk

Abstract: Objective This study evaluated the presence and the levels of antibodies reactive to SARS-CoV-2 S1 and S2 subunits (S1 + S2), and nucleocapsid protein. Study design The levels of SARS-CoV-2 S1 + S2-and nucleocapsid-reactive SIgM/IgM, IgG and SIgA/IgA were measured in human milk samples from 41 women during the COVID-19 pandemic (2020-HM) and from 16 women 2 years prior to the outbreak (2018-HM). Results SARS-CoV-2 S1 + S2-reactive SIgA/IgA, SIgM/IgM and IgG were detected in 97.6%, 68.3% and 58.5% in human milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 35 publications
5
88
2
4
Order By: Relevance
“…Although in mammals, the IgG is transferred through the placenta and breast milk, in fish the IgM plays this role in the yolk 21 . Similarly, in humans, the presence of SARS-CoV-2 antibodies in breast milk has been found to provide passive immunity for children, to protect them 22,23 . In this sense, the antibody transfer shown in zebrafish could be helpful in future studies to understand the maternal immunological protection of descendants against SARS-CoV-2 or any other vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Although in mammals, the IgG is transferred through the placenta and breast milk, in fish the IgM plays this role in the yolk 21 . Similarly, in humans, the presence of SARS-CoV-2 antibodies in breast milk has been found to provide passive immunity for children, to protect them 22,23 . In this sense, the antibody transfer shown in zebrafish could be helpful in future studies to understand the maternal immunological protection of descendants against SARS-CoV-2 or any other vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies that bind to S1 or S2 subunit could block the attachment or fusion of SARS-CoV-2. Our recent study demonstrated human milk antibodies’ presence reactive to SARS-CoV-2 S1 + S2 subunits in milk from mothers during the COVID-19 pandemic [ 18 ]. However, the levels in antibodies specific to S1 and S2 subunits from SARS-CoV-2 in mothers with confirmed COVID-19 PCR remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that S1 + S2-reactive SARS-CoV-2 SIgA/IgA and SIgM/IgM were detected in most human milk samples collected during COVID-19, but mothers did not have a confirmed PCR test [ 18 ]. These mothers had viral symptoms associated with COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…These results are reassuring and all postnatal mothers irrespective of their COVID status should be encouraged to exclusively breastfeed their babies and follow general safety precautions. Moreover, SARS-CoV-2reactive antibodies in breast milk may also provide passive immunity to breastfed infants and protect them against COVID-19 [6].…”
Section: Discussionmentioning
confidence: 99%